2012
DOI: 10.1002/stem.789
|View full text |Cite
|
Sign up to set email alerts
|

Preconditioning by Phosphodiesterase-5 Inhibition Improves Therapeutic Efficacy of Adipose-Derived Stem Cells Following Myocardial Infarction in Mice

Abstract: The rationale of this article is enhancing the therapeutic potential of stem cells in ischemic microenvironments by novel preconditioning strategies is critical for improving cellular therapy. We tested the hypothesis that inhibition of phosphodiesterase-5 (PDE-5) with sildenafil (Viagra) or knockdown with a silencing vector in adipose-derived stem cells (ASCs) would improve their survival and enhance cardiac function following myocardial implantation in vivo. ASCs were treated with sildenafil or PDE-5 silenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 44 publications
1
47
0
1
Order By: Relevance
“…The in vivo effect was also associated with increased vascular density and decreased cardiac fibrosis. Overall, the protective effect of modified cells was suggested to be due to increased duration and release of paracrine factors in the ischaemic myocardium [62]. Figure 1 summarizes the effects of stem cell modifications on cardiac fibrosis following MI.…”
Section: Stem Cell Modifications and Cardiac Fibrosismentioning
confidence: 99%
“…The in vivo effect was also associated with increased vascular density and decreased cardiac fibrosis. Overall, the protective effect of modified cells was suggested to be due to increased duration and release of paracrine factors in the ischaemic myocardium [62]. Figure 1 summarizes the effects of stem cell modifications on cardiac fibrosis following MI.…”
Section: Stem Cell Modifications and Cardiac Fibrosismentioning
confidence: 99%
“…For example, sildenafil or short hairpin RNA was used for preprocessing to inhibit ADSC to express phosphodiesterase 5, which improved the therapeutic effect of intramyocardial injection of ADSC after myocardial infarction in mice. [65] 5 Cell-free therapy…”
Section: Pretreatmentmentioning
confidence: 99%
“…For example, studies have now shown that MSC protein extracts or con- ditioned medium collected from MSC cultures can produce many of the same beneficial effects as MSCs on the post-infarction heart and in damaged liver tissues [69,70]. MSCs appear to secrete VEGF and basic fibroblast growth factor (bFGF) upon contacting the injured myocardium, which stimulates the formation of new vessels and increases the capillary density to increase/restore blood flow to the infarcted region [71]. However, the secretory activity of MSCs strongly depends on their tissue microenvironmental conditions.…”
Section: Enhanced Secretion Effectsmentioning
confidence: 99%